Decoding the neural mechanisms of human tool use - Gallivan, Jason P; McLean, D Adam; Valyear, Kenneth F; Culham, Jody C (eLife, 2013)
Sophisticated tool use is a defining characteristic of the primate species but how is it supported by the brain, particularly the human brain? Here we show, using functional MRI and pattern classification methods, that tool use is subserved by multiple distributed action-centred neural representations that are both shared with and distinct from those of the hand. In areas of frontoparietal cortex we found a common representation for planned hand- and tool-related actions. In contrast, in parietal and occipitotemporal regions implicated in hand actions and body perception we found that coding remained selectively linked to upcoming actions of the hand whereas in parietal and occipitotemporal regions implicated in tool-related processing the coding remained selectively linked to upcoming actions of the tool. The highly specialized and hierarchical nature of this coding suggests that hand- and tool-related actions are represented separately at earlier levels of sensorimotor processing before becoming integrated in frontoparietal cortex. The use of tools is a key characteristic of primates. Chimpanzees—our closest living relatives—use sticks to probe for termites as well as stones to crack open nuts, and have even been seen using specially sharpened sticks as spear-like tools for hunting. However, despite its importance in human evolution, relatively little is known about how tool use is supported by the brain. One possibility is that the brain areas involved in controlling hand movements may also begin to incorporate the use of tools. Another is that distinct brain areas evolved to enable tool use. To test these ideas, Gallivan et al. scanned the brains of human subjects as they reached towards and grasped an object using either their right hand or a set of tongs. The tongs had been designed so that they opened whenever the subjects closed their grip, thereby requiring subjects to perform a different set of movements to use the tongs as opposed to their hand alone. Three distinct patterns of brain activity were observed. First, areas previously linked to the processing of hand movements and the human body were found to represent actions of the hand alone (and not those of the tool), whereas areas previously linked to the processing of tools and tool-related actions represented actions of the tool alone (and not those of the hand). Second, areas of motor cortex implicated in the generation of movement represented actions performed with both the hand and the tool, but showed distinct activity patterns according to which of these was to be used. Lastly, areas associated with high-level cognitive and action-related processing showed similar patterns of activity regardless of whether the subjects were about to use the tongs or just their hand. Given that use of the hand and tool required distinct patterns of muscle contractions, this suggests that these higher-level brain regions must be encoding the action itself rather than the movements needed to achieve it. This study is one of the first to use functional neuroimaging to examine real as opposed to simulated tool use, and increases our understanding of the neural basis of tool use in humans. This knowledge could ultimately have applications for the development of brain-machine interfaces, in which electrodes implanted in motor regions of the brain are used to control prosthetic limbs.